Contour Ridge Tillage for Improved Crops and Fodder Trees Production in the Villages of Kani and Noumpinesso, Southern- Mali - Dembele, Cheick Oumar; Traore, Kalifa; Karembe, Moussa; Zemadim, Birhanu; Cisse, Fotigui; Samake, Oumar (Journal of Agricultural Studies, 2021)
In rural Mali shortage of livestock feed is a challenging phenomenon worsening day by day, particularly in the villages of Kani and Noumpinesso. The significant decrease in crops yield and livestock are due to persistent and continuous land degradation and over grazing. Soil water erosion and inappropriate or ineffective farming systems led to land degradation over the many years. A purposeful growing of fodder plant (fast growing trees species) and crops in interacting combinations for a range of benefits would be required using a technology that is easily adaptable by the rural farming communities. Contour ridge (CR) technology is a holistic approach that protects farmlands from erosion; increases soil moisture, nutrient availability for crops and associated fast growing trees. The CR technology in combination with forage and improved crop production systems were applied in Kani and Noumpinesso villages of southern Mali and resulted indicated that at the end of rainy season of 2017 and 2018 the application of CR technology significantly increased (p < 0.05) Gliricidia sepium and Leucaena leucocephala growth and development. Similar to 2017, in 2018 CR technology significantly increased (p < 0.05) sorghum, millet, maize, and cotton growth, yield, and economic benefit. At Kani during 2017 and 2018 season soil moisture was always significantly higher (p < 0.05) under fodder planted area than non-fodder planted area, and the difference was high with respect to farmlands without CR.